Complexity of hydrogeologic regime around an ancient low‐angle thrust fault revealed by multidisciplinary field study. Issue 4 (28th September 2016) - Mundy, E. M.; Dascher‐Cousineau, K.; Gleeson, T.; Rowe, C. D.; Allen, D. M.
Abstract: Co‐located and integrated observation of the surface and subsurface is necessary to characterize fault zone hydrogeology. The spectacular cliff‐face exposure of the Champlain Thrust fault at Lone Rock Point, Vermont, and a nearby well‐field site provides the opportunity for co‐located structural and hydrogeologic field observations. We mapped the prominent structural features of the Champlain Thrust fault and discrete groundwater seeps in outcrop, and also drilled through the fault near the outcrop and determined aquifer parameters from aquifer pumping tests. In outcrop, the fault core thickness varies on the meter scale, splays out into multiple strands, and is offset by a minor normal fault. Groundwater seeps are prevalent in the heavily fractured footwall, but limited in the fault core and hanging wall, suggesting that at the cliff face the water table is generally near the fault core and groundwater flow in the hanging wall is limited. Enrichment of more soluble minerals in cemented fault rock associated with older strands of the fault system may play an important role in localizing karst features in the hanging wall. At the well‐field site, the Champlain Thrust fault is offset significantly by a high‐angle normal fault, the water table is near the surface, and aquifer pumping tests reveal a complex hydrogeologic system, with karst and steep fractures as strong hydraulic conduits in the hanging wall and fault core. The most salient features of the fault zone hydrogeology in the surface and subsurface data are different, but can be integrated into a preliminary conceptual model. Together, the surface and subsurface methods underscore and emphasize the complexity and heterogeneity of the hydrogeology of this low‐angle sedimentary fault.